The prevention of musculoskeletal injuries in basketball players: the systematic development of an intervention and its feasibility - Stefani Souza Silva, M. (British Journal of Sports Medicine, 2021)
Background Acute and overload injuries are common among basketball players, especially in the lower limbs. Injuries are detrimental to both individual and team performance, such as negative injury consequences, loss of productivity and high cost of health care, and are critical components of any sport.